Türkiye de Eğitim Bilimleri Alanında Geri Bildirim Üzerine Yapılmış Lisansüstü Tezlerin Analizi - ÖZALP, M. TALHA (Necmettin Erbakan University, 2022)
Feedback is the information given to define the difference between the student’s performance and the targeted performance in the education process and to increase the student’s performance to the desired level. It can be used effectively both in the learning-teaching process and in the measurement and evaluation process. In the relevant literature, there are experimental and descriptive studies on the use of feedback in different fields. However, there seems to be no study on the panorama and status of research on feedback. In this context, the study aims to examine the Turkish educational sciences literature on feedback. In accordance with the purpose of the research, the document analysis technique was used in line with the qualitative methodology. In the research, a total of 83 postgraduate theses on the website of the Higher Education Institution were examined. Content analysis method was used in the analysis of the collected data. As a result of the research, it was determined that the theses prepared on feedback were mostly prepared at the graduate level and mostly in 2019. It was determined that the interview technique was mostly used as a data collection tool in the prepared theses. In addition, according to the results obtained in the research, it was determined that the effects of feedback on writing skills and academic success/learning were mostly investigated in thesis studies prepared on feedback.
Keywords: 4. Education